2004
DOI: 10.1111/j.1464-5491.2004.01288.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemia and driving in people with insulin‐treated diabetes: adherence to recommendations for avoidance

Abstract: Compliance with statutory requirements to inform the licensing authority and motor insurer is good, and drivers' perceptions of the minimum safe blood glucose level for driving are encouraging. However, most drivers rely on symptoms to detect hypoglycaemia while driving, and seldom test blood glucose before driving. Patient education should emphasize the role of blood glucose monitoring in relation to driving, and highlight the potential deterioration in driving performance when blood glucose falls below 4.0 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
65
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 26 publications
8
65
0
3
Order By: Relevance
“…• не останавливаю транспортное средство, если во время вождения у меня развивается гипогликемия; • убежден/а, что минимальный уровень глюкозы крови для безопасного вождения может быть менее 3,0 ммоль/л [20]. Большая часть водителей, отметивших, что не из-меряют уровень глюкозы крови перед поездкой, кроме того, имели нарушенную чувствительность к гипогли-кемиям.…”
Section: сахарный диабет Diabetes Mellitusunclassified
“…• не останавливаю транспортное средство, если во время вождения у меня развивается гипогликемия; • убежден/а, что минимальный уровень глюкозы крови для безопасного вождения может быть менее 3,0 ммоль/л [20]. Большая часть водителей, отметивших, что не из-меряют уровень глюкозы крови перед поездкой, кроме того, имели нарушенную чувствительность к гипогли-кемиям.…”
Section: сахарный диабет Diabetes Mellitusunclassified
“…18 This suggests that driving accidents associated with this clinical problem are relatively uncommon. This may be a consequence of more frequent blood glucose monitoring by drivers who have some degree of impaired awareness, 2 or their voluntary cessation of driving when loss of awareness becomes severe. Reduction in length of time of revocation of a driving licence from 12 to 3 months The most powerful factor for predicting the risk of severe hypoglycaemia is a history of severe hypoglycaemia, as was shown in the 30-year analysis of the DCCT/EDIC data.…”
Section: How Have the Eu Driving Regulations Changed In The Uk From Jmentioning
confidence: 99%
“…One survey of drivers with insulin-treated diabetes suggested that 13% had experienced hypoglycaemia while driving during the preceding year. 2 …”
Section: Why Is Diabetes Potentially Dangerous For Drivers?mentioning
confidence: 99%
See 1 more Smart Citation
“…7 However, research suggests that as few as 15% of adults routinely perform SMBG before driving. 15,16 As a large tertiary diabetes care center in the mid-Atlantic, our practice is uniquely poised to evaluate associations among state-directed driver's license requirements, physician involvement, and type 1 diabetes control. We routinely see adolescent patients in the Washington, D.C., metro area, including patients from Maryland and Northern Virginia.…”
Section: License To Drive: Type 1 Diabetes Management and Obtaining Amentioning
confidence: 99%